Measurement and calibration of non-linear shear terms in galaxy cluster fields - Liu, Binyang; Dell’Antonio, Ian; Chotard, Nicolas; Clowe, Douglas (Frontiers in Astronomy and Space Sciences, 2024)
IntroductionGalaxy cluster lensing is a powerful tool for measuring the mass of galaxy clusters, but accurate shear measurement and calibration are critical to obtaining reliable results. This study focuses on the measurement and calibration of weak lensing shears to improve mass estimates in cluster lensing. To deal with the problem, we first developed an image simulation pipeline, jedisim, which utilizes galaxy images extracted from the Hubble Space Telescope (HST) Ultra Deep Field (UDF) and the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS).MethodsThe simulations represent realistic galaxy distributions and morphologies as input sources. The foreground halo with a Navarro–Frenk–White (NFW) profile is constructed such that the lensing signals of background galaxies can be measured by the Vera C. Rubin Observatory’s Legacy Survey of Space and Time (LSST) Science Pipelines. By comparing the measured reduced shear gmeas and the true reduced shear gtrue, we observe non-linearity up to g≲0.6. We fit polynomials to the data with quadratic correction adequate to g≲0.4. Meanwhile, we conduct mass estimates using the pzmassfitter code on four different clusters.ResultsThe mass estimate results are significantly improved after applying the shear calibration derived from the present work—from 4.954±0.504×1014M⊙ to 10.507±0.498×1014M⊙ after calibration for a simulated cluster with the mass of 10×1014M⊙. In multiple cases of validation, the estimated results are all consistent with true cluster mass.DiscussionThis study yields the first relationship between reality and shape measurement of the LSST Science Pipelines and serves as the first step toward the overall goal of mass calibration in cluster lensing. By addressing the challenges in shear measurement and calibration, we aim to enhance the accuracy and reliability of mass estimates in galaxy cluster lensing studies.